Invariants and Lacunae in Translation of Russian Interjectional Phrases: A Study of English Translations of M. A. Bulgakov's “The Master and Margarita” - A. S. Izvolenskaya (Научный диалог)
This article explores the peculiarities of identifying and overcoming linguocultural lacunae in translated literary texts, specifically focusing on the stylistic material of M. A. Bulgakov's novel “The Master and Margarita.” By employing an inductive method of linguistic-cognitive analysis, we identify several implicit lacunae. The main findings are as follows: 1) The invariants revealed during the analysis of the translated literary text serve as a means to bridge significant linguistic and cultural lacunae; 2) Analyzing certain translation choices can provide material for investigating the nature of lacunae and their existence within literary texts from both synchronic and diachronic perspectives. We propose a structure for an academic translation commentary designed to integrate the artistic narrative into its historical context, thereby addressing substantial lacunae. The commentary is viewed as an integral part of the translation and the creative translation process. This study examines the following translations of “The Master and Margarita”: by Michael Glenny (1967), Mirra Ginsburg (1967), Diana L. Burgin and Katherine T. O'Connor (1993), Richard Pevear and Larissa Volokhonsky (1997), and Hugh Aplin (2008).